Association Of Tinnitus With Depression And Anxiety In Hypertensive Patients - Tabassum, Maria; Rehman, Atia Ur; Ashraf, Tahira; ali, Safder; Tahira, Azmat; Nomani, Tahira (International Journal of Rehabilitation and Special Education (IJRSE), 2021)
Background: Tinnitus is a condition that can be objective or subjective. The form of tinnitus most often associated with psychosocial co-morbidities is subjective tinnitus.Objective: The aim of our study was to determine the association of tinnitus with depression and anxiety in hypertensive patients.Methodology: It was cross sectional study. A total of 159 (100) % patients with hypertension were screened for presence of tinnitus in medical outpatient department of district headquarter hospital Vehari from July 2020 to March 2021. All of them were asked to complete a standardized Tinnitus handicap inventory questionnaire (THI) to assess severity of tinnitus followed by otoscopy. Depression and anxiety were measured using the Beck depression and anxiety inventories.Results: Tinnitus is strongly linked to anxiety and depression, according to the findings.Conclusions: All tinnitus patients should be screened for mental illness because of the strong connection between tinnitus, depression, and anxiety. These complex disorders should be handled by a multidisciplinary team that includes cognitive behavioral treatment and likely pharmacological therapy.